Analisis Tingkat Literasi Media Pada Anak Kos dalam Menggunakan Media Sosial - Icha Angel Sagala; Melly Br Bangun; Lizza Azzahra; Seni Rasbina Br Karo Sekali (CV. Eracita Grup, 2026)
This study aims to describe the level of environmental literacy and cleanliness behavior among Generation Z in Medan Sunggal City. The research involved 50 respondents and employed a questionnaire instrument covering environmental knowledge, attitudes, awareness, waste management behavior, daily hygiene habits, and social responsibility toward the environment. Data were collected using a 1–5 Likert scale reflecting respondents’ perceptions and actions related to environmental issues. The data were analyzed using descriptive statistical analysis to identify trends in environmental literacy and cleanliness behavior. The results indicate that Generation Z demonstrates a generally good level of environmental literacy, particularly in understanding the impacts of waste, plastic usage, and the importance of maintaining public cleanliness. Cleanliness behavior also tends to be positive, as reflected in proper waste disposal practices, reduced use of plastic, and efforts to maintain cleanliness in both public and personal spaces. However, certain aspects, such as consistent waste sorting and active participation in environmental initiatives, still require improvement. These findings highlight the importance of strengthening environmental education and providing adequate facilities to support sustainable and environmentally responsible behavior among Generation Z.